2022
DOI: 10.1101/2022.09.09.507306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative analysis of CRISPR off-target activity discovery tools followingex vivoediting of CD34+hematopoietic stem and progenitor cells

Abstract: While CRISPR-based editing most often occurs at DNA sequences with perfect homology to the guide RNA (gRNA), unintended editing can occur at highly homologous regions (i.e., off-target (OT) sites). Due to the pace at which genome editing therapies are approaching clinical applications, there is an emerging need to define effective workflows for investigating OT editing effects. A number of homology-dependent, in silico-based prediction methods and wet lab-based empirical methods exist to investigate OT editing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In spite of these myriad strategies for detection of off-target indels, recent work has shown that ex vivo editing in HSPCs elicits very few bona fide off-target sites (<1 true off-target site per gRNA) when using clinically relevant workflows ( Cromer et al, 2022b ). Of bona fide sites, all were highly homologous to the target sequence and predicted by the majority of in silico methods included in the study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of these myriad strategies for detection of off-target indels, recent work has shown that ex vivo editing in HSPCs elicits very few bona fide off-target sites (<1 true off-target site per gRNA) when using clinically relevant workflows ( Cromer et al, 2022b ). Of bona fide sites, all were highly homologous to the target sequence and predicted by the majority of in silico methods included in the study.…”
Section: Introductionmentioning
confidence: 99%
“…While the degree to which tissue-of-origin could be gleaned from this approach has yet to be fully explored, the investigation of on- and off-target CRISPR activity at expected cleavage sites in cfRNA could determine whether intended or unintended genome editing results in changes to the transcriptome. Since sites of CRISPR off-target activity typically reside in intergenic regions of the genome with no known functional significance ( Cromer et al, 2022b ), it is possible that CRISPR activity will be detected in cfDNA, but not in transcribed cfRNA. This could be an important measure to assay efficacy and safety of in vivo editing immediately following therapeutic delivery as well as over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the feasibility of detecting off-target mutations by WGS, we utilized the in silico Cas-OFFinder tool to identify off-target sites based on sequence homology to the gRNA sequences and the total number of off-target sites when allowing for up to 9 mismatches between the gRNA and off-target sequence is provided in Supplementary Table S4 . While off-target editing can occur at sites with up to 4 mismatches ( Pattanayak et al, 2013 ; Cromer et al, 2022 ), we focused on assessing the WGS data at 93 predicted off-target regions that contained 2 or 3 mismatches which occurs more commonly. De novo mutations within individual blastomeres were identified by WGS in 16 predicted off-targeted sites of which 7 were located within genes and nine were located in intergenic regions ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results confirmed that off-target editing could be assessed by WGS in individual blastomeres, although we used a biased in silico method that relied on assessing targets with sequence homology and did not evaluate potential targets with greater than three mismatches. Additional in silico nominated targets should be evaluated to fully assess the impact of off-target editing as CRISPR-Cas9 cleavage can occur at off-target sites with up to four mismatches ( Pattanayak et al, 2013 ; Cromer et al, 2022 ). Moreover, unbiased methods that survey the whole genome without prior knowledge or prediction of sequence homology would be more informative, yet there is not a current superior method or technique for this analysis ( Chaudhari et al, 2020 ; Atkins et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%